Virulence and Antibiotic Resistance Genes in Listeria monocytogenes Strains Isolated From Ready-to-Eat Foods in Chile - Parra-Flores, Julio; Holý, Ondrej; Bustamante, Fernanda; Lepuschitz, Sarah; Pietzka, Ariane; Contreras-Fernández, Alejandra; Castillo, Claudia; Ovalle, Catalina; Alarcón-Lavín, María Paula; Cruz-Córdova, Ariadnna; Xicohtencatl-Cortes, Juan; Mancilla-Rojano, Jetsi; et al. (Frontiers in Microbiology, 2022)
Listeria monocytogenes is causing listeriosis, a rare but severe foodborne infection. Listeriosis affects pregnant women, newborns, older adults, and immunocompromised individuals. Ready-to-eat (RTE) foods are the most common sources of transmission of the pathogen This study explored the virulence factors and antibiotic resistance in L. monocytogenes strains isolated from ready-to-eat (RTE) foods through in vitro and in silico testing by whole-genome sequencing (WGS). The overall positivity of L. monocytogenes in RTE food samples was 3.1% and 14 strains were isolated. L. monocytogenes ST8, ST2763, ST1, ST3, ST5, ST7, ST9, ST14, ST193, and ST451 sequence types were identified by average nucleotide identity, ribosomal multilocus sequence typing (rMLST), and core genome MLST. Seven isolates had serotype 1/2a, five 1/2b, one 4b, and one 1/2c. Three strains exhibited in vitro resistance to ampicillin and 100% of the strains carried the fosX, lin, norB, mprF, tetA, and tetC resistance genes. In addition, the arsBC, bcrBC, and clpL genes were detected, which conferred resistance to stress and disinfectants. All strains harbored hlyA, prfA, and inlA genes almost thirty-two the showed the bsh, clpCEP, hly, hpt, iap/cwhA, inlA, inlB, ipeA, lspA, mpl, plcA, pclB, oat, pdgA, and prfA genes. One isolate exhibited a type 11 premature stop codon (PMSC) in the inlA gene and another isolate a new mutation (deletion of A in position 819). The Inc18(rep25), Inc18(rep26), and N1011A plasmids and MGEs were found in nine isolates. Ten isolates showed CAS-Type II-B systems; in addition, Anti-CRISPR AcrIIA1 and AcrIIA3 phage-associated systems were detected in three genomes. These virulence and antibiotic resistance traits in the strains isolated in the RTE foods indicate a potential public health risk for consumers.